PENGARUH KEPUTUSAN PENDANAAN, PERTUMBUHAN PERUSAHAAN, KEPUTUSAN INVESTASI, DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Food and Beverege yang Terdaftar di Bursa Efek Indonesia 2018-2021) - Neneng Hasanah (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
This study was conducted to examine and analyze the effect of funding decisions, company growth, investment decisions and dividend policies on firm value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange 2018-2021. This study uses secondary data. Data obtained from the IDX website. The population in this study are food and beverage manufacturing sub-sector companies listed on the Indonesia Stock Exchange in 2018-2021. The technique for collecting samples in this study is purposive sampling. Based on the criteria that have been determined by the researcher, there are 11 samples of companies of food and beverage. The data analysis technique used multiple linear regression using SPSS. The results of this study indicate that funding decisions, investment decisions and dividend policies have no effect on firm value. While the growth of the company has an effect on the value of the company.